Diversity or disadvantage?: Putnam, Goodhart, ethnic heterogeneity, and collective efficacy - Twigg, Liz (Environment and planning, 2010)
Recent debates have suggested that increasing social diversity within Western economies is associated with adverse social consequences such as loss of community and decline of civic society, including an erosion of collective efficacy (ie shared expectations of and mutual engagement by residents in social control). In the UK and US, these debates have been given impetus by concerns about the effects of growing ethnic heterogeneity on community life. Here there is an assumption that heterogeneity undermines social cohesion and makes the established population less willing to share resources, trust fellow citizens, so that it eventually ‘hunkers down’ and withdraws from collective life. To date there are few studies that have examined this in detail across England at the small-area level. The research presented here explores this terrain by exploiting information from the British Crime Survey on two recognised dimensions of collective efficacy: namely, social cohesion and trust, and informal social control. Multivariate, multilevel models were used to determine the importance of individual and area characteristics in the possible explanation of these outcomes, and particular attention was paid to the relative importance of neighbourhood disadvantage over and above neighbourhood diversity. Results suggest that both diversity and disadvantage are statistically associated with reduced levels of social cohesion and trust, and informal social control, but greater substantive importance is attached to neighbourhood disadvantage.